Factor analysis of women's low awareness in cervical cancer screening - Azlina, Fitri Ayatul; Firdausi, Rieh; Marisa, Vena; Raudah, Siti Hizratul; Husna, Rezkia Asma’ul; Fatiniah, Nabillah (Media Keperawatan Indonesia, 2024)
Cervical cancer is a type of cancer that causes high mortality and morbidity rates in women. Women's awareness of screening to prevent cervical cancer is still low. This study aims to analyze the factors that cause women's low awareness of cervical cancer screening. This research uses a correlational design with a cross sectional approach. The total sample was 94 people with the criteria being women aged 15 to 59 years, married, living with their husband, and domiciled in Sungai Rangas Ulu Village. The sampling technique used was purposive sampling. This study used questionnaire A in the form of demographic data and questionnaire B in the form of a questionnaire about knowledge, attitudes and satisfaction with health workers. Data collection was carried out in July-August 2023. in Sungai Rangas Ulu Village in West Martapura District, Banjar Regency. The research questionnaire was filled out directly by research respondents at their homes. The results of the Chi Square test obtained a p value of 0.038, which means there is a relationship between knowledge and attitude and the Chi Square test obtained a p value of 0.013, which means there is a significant relationship between satisfaction with health workers and attitude. The results of the multiple linear regression test obtained a sig level. of 0.000 that knowledge and satisfaction have a role in women's attitudes with a beta value of 0.575 as the most dominant factor influencing women's attitudes towards cervical cancer screening. Women's knowledge and satisfaction with health workers plays an important role in influencing women's attitudes towards cervical cancer screening.